WOMAN’S STRENGTH IN EKA KURNIAWAN’S NOVEL BEAUTY IS A WOUND - T. Raja Mulia; Pardi Pardi (Universitas Islam Sumatera Utara, 2020)
The research aims to reveal the woman’s strength in Eka Kurniawan’s novel entitled Beauty Is a Wound. Strength is the emotional qualities necessary in dealing with situation or events that are distress or difficult. Strength is divided into two categories. They are strength to be tough and strength to solve the problem. The research design adopted in this study is descriptive qualitative, and the approach applied is adopting feminism one as this research describes the strength of the first female character by the name of Dewi Ayu. Dewi Ayu, as the protagonist, is reflected as a classy prostitute in Indonesia town of Halimunda. She is an indonesian-netherlands crossbreed. She is beautiful, cold, practical, logical, at the same time full of sympathy and she is also a good mother. She never tears herself. She has high adrenalin in her self. She never feels tired to do something. This story inspires all people to have more strength and tough to go on in life. Furthermore, the finding of this study shows that Dewi Ayu has strength to be tough and to solve her complicated problems.